Few-layered two-dimensional molecular crystals for organic artificial visual memories with record-high photoresponse. Issue 28 (12th July 2021) - Zhang, Lijuan; Tian, Xinzi; Yao, Jiarong; Song, Xianneng; Yang, Shuyuan; Guo, Siyu; Wang, Ying; Li, Bin; Ren, Xiaochen; Sun, Yan; Yang, Fangxu; Li, Rongjin; et al.
Abstract : Molecularly thin two-dimensional molecular crystals (2DMCs) were used to construct artificial visual memories with high photoresponse. Abstract : Artificial visual memories (AVMs) are crucial to many technologies, including artificial intelligence, humanoid robots, and visual prostheses. Most studies used a thick polycrystalline film as the AVM active layer to achieve a continuous channel for charge collection. However, because of the inherent interlayer shielding effect in thick films, both photogating and electrical gating are inefficient and the photoresponse of these AVMs is extremely low. Herein, the obstacle of the interlayer shielding effect in thick films is overcome by using molecularly thin two-dimensional molecular crystals (2DMCs). Because of the highly efficient photogating and electrical gating effects of 2D channels, the developed AVMs based on few-layered 2DMCs show record-high photoresponse. The AVMs also exhibited multilevel non-volatile memory functionality, with long retention time and excellent write–erase stability, by exploiting the persistent photoconductivity effect.